RETICULOCYTE HEMOGLOBIN COUNT AS A DIAGNOSTIC MARKER OF FUNCTIONAL IRON DEFICIENCY IN BREAST CANCER PATIENTS IN LAHORE (Journal of Medical & Health Sciences Review, 2026)
One of the most common and clinically important complications of breast cancer patients is anemia, which is one of the primary causes of fatigue, functional disability, quality of life, and excessive treatment outcomes. The most common etiologies of cancer-related anemia include defects in iron metabolism, especially functional iron deficiency, which is often underrated. Functional iron deficiency is defined by sufficient or excessive iron stores and non-optimal supply of iron to erythropoiesis, which is mainly inspired by upregulation of hepcidin through inflammation. Traditional iron biomarkers like serum ferritin and transferrin saturation are not usually useful in malignancy as ferritin acts as an acute-phase reactant, and iron transferrin saturation becomes inflammatory activity-dependent. The reticulocyte hemoglobin parameters are the parameters presented in terms of reticulocyte hemoglobin equivalent or reticulocyte hemoglobin content which contain the iron to be Iron restricted erythropoiesis is monitored in real time by the reticulocyte hemoglobin parameters. This review is a critical review of the biological basis, diagnostic performance, and clinical utility of reticulocyte hemoglobin measurement to diagnose functional iron deficiency in patients with breast cancer, and how the measurement is applied to clinical practice as pertinent to oncology practice, in Lahore, Pakistan.